Mixed Adenoneuroendocrine Carcinoma of the Small Bowel in a Patient with Crohn's Disease: A Case Report - Kim, Kwang-Min; Bae, Kyung Eun; Kim, Jae Hyung; Jeong, Myeong Ja; Kim, Soung Hee; Kim, Ji-Young; Kim, Soo Hyun; Lee, Jihae; Kang, Mi-Jin; Kim, Tae Gyu (Journal of the Korean Society of Radiology, 2019)
Mixed adenoneuroendocrine carcinoma (MANEC) is a rare tumor of the gastrointestinal tract that has both exocrine and neuroendocrine components. There are only 5 case reports about this combined tumor in the small bowel, arose in a background of long-standing Crohn’s disease. Here, we report a case of small bowel MANEC in a 54-year-old male with Crohn’s disease, who presented a heterogeneous enhancing, asymmetric small bowel wall thickening with small bowel obstruction and had a difficulty in differential diagnosis before surgery.